2021
DOI: 10.1002/jsp2.1167
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized histopathology scoring system for human intervertebral disc degeneration: an Orthopaedic Research Society Spine Section Initiative

Abstract: Background: Histopathological analysis of intervertebral disc (IVD) tissues is a critical domain of back pain research. Identification, description, and classification of attributes that distinguish abnormal tissues form a basis for probing disease mechanisms and conceiving novel therapies. Unfortunately, lack of standardized methods and nomenclature can limit comparisons of results across studies and prevent organizing information into a clear representation of the hierarchical, spatial, and temporal patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 102 publications
(136 reference statements)
0
44
0
1
Order By: Relevance
“…It is also important to note that human disc histopathology studies have revealed that not all degenerated discs exhibit calcification of the CEPs. 137 Therefore, this work sought to capture models of each grade with and without calcification, despite the limitation of generic models of each grade with mean parameters rather than a range of plausible bounds to the mean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that human disc histopathology studies have revealed that not all degenerated discs exhibit calcification of the CEPs. 137 Therefore, this work sought to capture models of each grade with and without calcification, despite the limitation of generic models of each grade with mean parameters rather than a range of plausible bounds to the mean.…”
Section: Discussionmentioning
confidence: 99%
“…From this work, we can only speculate that the effect of calcification becomes more pertinent at Grade V, which we have already deemed too degenerated for cell‐based regeneration. It is also important to note that human disc histopathology studies have revealed that not all degenerated discs exhibit calcification of the CEPs 137 . Therefore, this work sought to capture models of each grade with and without calcification, despite the limitation of generic models of each grade with mean parameters rather than a range of plausible bounds to the mean.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of this homeostatic balance is multifactorial, and may start at the cellular level caused by, for example, nutrient deprivation due to ossification of the endplates, or could initiate via a structural defect that can cause subsequent cellular changes. 28 The regulation of cellular turnover is vital to tissue homeostasis.…”
mentioning
confidence: 99%
“…This review focuses on the nucleus pulposus cells of the human IVD. For representative examples of the other species used in disc (patho)biology the reader is referred to the recent series of a multi-species histopathological grading schemes reported for mice ( Melgoza et al, 2021 ), rats ( Lai et al, 2021 ), rabbits ( Gullbrand et al, 2021 ), large animal ( Lee et al, 2021 ), and human ( Le Maitre et al, 2021 ) discs.…”
Section: The Intervertebral Discmentioning
confidence: 99%